A PSYCHO-SOCIOLOGICAL APPROACH TO THE THEME OF EVOLUTION AS SEEN IN BAMA’S KARUKKU. - Gayathri, M.; V, Sunitha. (International Journal of Psychosocial Rehabilitation, 2020)
Dalit writer Bama’s work Karukku, is packed with the pivotal theme of Dalit oppression that was dealt in a psycho-sociological plane. The entire psychological trauma, the author-narrator faced as a first-hand experience by her and which is later served as a collective consciousness of the whole marginalised lot is found remarkable. All the discussion undertaken here is seen with the glass of evolution in this research article that talks about various phases of evolution like that of Psychological, sociological and revolutionary aspect of the entire class-struggle. The very concept oppression itself is seen as a psychological and at last sociological evolution among the oppressed and the oppressor. In the similar manner eradication of such social evil is dealt as something that can be gradually done. Thus the evolution of self-realisation of Untouchability in the part of the narrator and then moving forward to create awareness on a social level is discussed here.